Paradigm of Post-Covid-19 Entrepreneurship Mindsets - Pipin Sukandi; Fariz Hanafsyah Umbara (Institute of Computer Science (IOCS), 2022)
It is undeniable that the consequences of the pandemic that has hit the whole world, including Indonesia, have had an extraordinary impact, especially on the wheels of the economy. Both large-scale companies are affected, in small and medium-sized companies. Life must be constant and entrepreneurs must still be able to run the economy. Mental surrender must stop the effort. However, with a different mindset, this pandemic can be used as a business opportunity. The respondents of this study were students at Widyatama University. The purpose of this research is to find out the mindset of business actors after the impact of Covid-19, using a descriptive analysis method to verify the research shows that the entrepreneurial mindset influences the intention to do entrepreneurship, besides that creativity is also found to have an influence on the intention to do entrepreneurship. With a change in mindset, the perpetrators began to increase their sales. Along with the end of the Covid-19 pandemic, there is a little enthusiasm for entrepreneurs to return to running it so that students who have businesses return to running their businesses accompanied by the start of face-to-face lectures so that they are more enthusiastic about running their businesses again.